The Effect of School Culture and Work Commitment on School Quality - Krisbiyanto, Achmad; Afinudin, Nadzif; Rahajeng, Cantik Tri (Chalim Journal of Teaching and Learning, 2024)
This study explores the impact of school culture and work commitment on the quality of education at YPI Al-Multazam Mojokerto, both individually and collectively. Employing a quantitative approach, data were gathered through questionnaires distributed to all teachers and staff using a total sampling technique. The independent variables, school culture and work commitment, were analyzed against the dependent variable, school quality. Hypothesis testing was conducted using t-tests (partial analysis) and f-tests (simultaneous analysis). Findings reveal that school culture significantly influences school quality, while work commitment alone does not show a notable effect. However, when combined, school culture and work commitment have a significant positive impact on school quality. These results underscore the importance of fostering a strong, positive school culture as a cornerstone for creating a supportive and conducive learning environment. Furthermore, the findings highlight the need to enhance teacher commitment to boost performance and productivity. This study provides valuable insights for educational institutions aiming to sustain and improve school quality by focusing on cultural values and employee dedication as key drivers of success